The link between over-subscription ratio and investor heterogeneity – evidence from Malaysian fixed-price IPOs - YONG, Othman; ALBADA, Ali; QATITI, Khalid AL; LOW, Soo-Wah (Asian Economic and Financial Review, 2025)
This paper examines the impact of investor demand, measured by the over-subscription ratio (OSR), on the divergence of opinion among prospective investors. The sample comprises 131 IPOs listed on Bursa Malaysia from 2010 to 2018. The results indicate that OSR significantly amplifies investors’ divergence of opinions, contributing to their different trading behaviors, and leading to greater underpricing and market inefficiency on the first day of listing. The effect is particularly pronounced for IPOs listed on the ACE Board and during hot issue periods. These findings highlight the significant negative impact of OSR on market efficiency and investor behavior on the first day of listing. They suggest that future issuers should consider pricing their IPO issues using the book-building method, which could reduce divergence of opinion and enhance overall market efficiency, despite the costlier pricing method. Finally, market participants, including investors and issuers, can leverage these insights to make more informed decisions in IPO markets that rely on the fixed-price method.